Characteristics of violence against women in Kairouan, Tunisia, in 2017. Issue 1 (1st January 2021) - Nihel, Haddad; Latifa, Merzougui; Anissa, Ajina; Raja, Guezel; Souheil, Mlayeh; Wael, Majdoub; Maher, Jedidi; Slah, Soui; Ben Dhiab, Mohamed
ABSTRACT: Violence against women represents a serious concern worldwide. In Tunisia, despite an advanced legislative framework, we still receive women victims of violence. This survey aimed to characterize the demographic and clinical profile of women victims of violence in Kairouan, central Tunisia. This survey was designed as a cross-sectional study. It concerned women victims of violence over 18 years old, consulting the emergency department of the University Hospital of Kairouan during 3 months in 2017. We defined violence against women according to the Tunisian protection of gender discrimination law. This survey included 100 Tunisian victims of violence; their median age was 35 (ranging from 18 to 59 years old). This study showed that 58% of victims, CI95% [48.3%, 67.6%], were illiterate or had only a primary level education and that 90%, CI95% [84.1%, 95.8%], had a low or middle socioeconomic level. The Intimate Partner Violence was about 70% among all cases, CI 95% [61.0%, 78.9%]. Most aggressive partners were young (aged between 39 and 51 years old). The most affected part of the body was the face (76%, CI 95% [67.6%, 84.3%]). Alcohol consumption was the primary risk factor of violence in 29.6% of cases, CI95% [20.0%, 37.9%]. Other risk factors were the occupational instability, conflicts with the family in-laws and infidelity. Violence against women remains widespread. Even strict legislations in Tunisia didn't protect women sufficiently from different types of violence. It mostly happens within intimate relationships. Therefore, surveillance and early intervention controlling risk factors are extremely important.